Combined ATRX/IDH1 immunohistochemistry predicts genotype of oligoastrocytomas. Issue 2 (27th July 2015) - Hewer, Ekkehard; Vajtai, Istvan; Dettmer, Matthias S; Berezowska, Sabina; Vassella, Erik
Abstract : Aims: To assess whether in oligoastrocytomas ATRX deficiency, as a surrogate of the alternative lengthening of telomeres (ALT) pathway,  has a role in predicting the presence or absence of loss of heterozygosity (LOH) of 1p and 19q, the genetic signature of oligodendroglial differentiation and a favourable prognostic marker. Methods and results: A series of 54 oligoastrocytomas were investigated by immunohistochemistry as well as microsatellite analysis for LOH 1p19q. Genetic findings were correlated with morphological assessment. Conclusions: ATRX deficiency was mutually exclusive with LOH. Conversely, ATRX‐proficient tumours immunoreactive for R132H‐mutant isocitrate dehydrogenase 1 (IDH1) showed a high rate (85%) of LOH. A more oligodendroglioma‐like morphology was associated with a higher rate of LOH even in the morphologically ambiguous group of oligoastrocytomas. Our findings support the concept that oligoastrocytomas represent a morphological grey zone, rather than a group of truly 'mixed' or 'intermediate' tumours. More precise classification of diffuse gliomas may also improve grading of borderline cases. We propose an immunohistochemical algorithm for classification of morphologically ambiguous diffuse gliomas.